2003
DOI: 10.4049/jimmunol.171.2.902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Cytomegalovirus Infection on Ligands for the Activating NKG2D Receptor of NK Cells: Up-Regulation of UL16-Binding Protein (ULBP)1 and ULBP2 Is Counteracted by the Viral UL16 Protein

Abstract: Human CMV (HCMV) interferes with NK cell functions at various levels. The HCMV glycoprotein UL16 binds some of the ligands recognized by the NK-activating receptor NKG2D, namely UL16-binding proteins (ULBP) 1 and 2 and MHC class I-related chain B, possibly representing another mechanism of viral immune escape. This study addressed the expression and function of these proteins in infected cells. HCMV induced the expression of all three ULBPs, which were predominantly localized in the endoplasmic reticulum of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 34 publications
11
107
0
Order By: Relevance
“…Also, several studies indicate increased NKR expression on T cells in CMV-infected individuals [31,50]. Interestingly, CMV downregulates expression of ligands for NKG2D (ULBP1 and ULBP2) and DNAM-1 (CD155, poliovirus receptor) on infected cells [51,52]. Downregulation of ligands for these NKR by CMV may promote persistent CMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies indicate increased NKR expression on T cells in CMV-infected individuals [31,50]. Interestingly, CMV downregulates expression of ligands for NKG2D (ULBP1 and ULBP2) and DNAM-1 (CD155, poliovirus receptor) on infected cells [51,52]. Downregulation of ligands for these NKR by CMV may promote persistent CMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…macrophages) or inducible by proinflammatory cytokines, and it is impaired by some virus molecules [53]. On the other hand, NKG2D ligands are displayed in HCMV-infected cells, and immune evasion mechanisms that interfere with their expression indirectly reflect the importance of the KLR in the anti-viral response [18,22,[27][28][29].…”
Section: Distribution Of Ilt2 Kir and Cd94/nkg2 Nkr On Hcmv-stimulatmentioning
confidence: 99%
“…The KLR activates NK cells and costimulates the response of CD8 + CTL against human cytomegalovirus (HCMV)-infected targets [18,26]; the identification of immune evasion mechanisms that interfere with surface expression of NKG2D ligands underline its importance in the antiviral response. The UL16 glycoprotein inhibits surface expression of MICB, ULBP1, ULBP2 [22,[27][28][29] and also interacts with RAET1G [24]. The gpUL142 HCMV molecule has been recently reported to down-regulate MICA [30].…”
Section: Introductionmentioning
confidence: 99%
“…NKG2D is expressed on all NK cells and a subset of T cells and recognizes stressinducible ligands including MHC class I chain-related gene A (MICA), MICB, and UL-16-binding proteins in humans (12). NKG2D ligands are found on many tumors and are up-regulated upon infection (13,14). Several studies have demonstrated that the enhanced cell surface expression of NKG2D ligands results in increased susceptibility of MHC I expressing tumors to NK cell cytotoxicity (15)(16)(17).…”
Section: N Atural Killer Cells Recognize Virus-infected and Tumormentioning
confidence: 99%